2021
DOI: 10.1039/d1ce00599e
|View full text |Cite
|
Sign up to set email alerts
|

Cation disorder and bond anharmonicity synergistically boosts the thermoelectric performance of p-type AgSbSe2

Abstract: AgSbSe2 is one of the important Te-free chalcogenides in I-V-VI2 semiconductors, shows attractive functional properties with enhancing thermoelectric performance. Here we report the thermoelectric performance of polycrystalline p-type AgSbSe2¬ nanostructured...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…clarified that the above mentioned “minimum thermal conductivity” in I‐V‐VI 2 semiconductors is limited solely by phonon‐phonon interactions [57] . Many studies have been performed to rationalize such a high thermal resistance, [53,57–60] and, as schematically shown in Figure 3, the underlying physical origins can be assigned to the following three reasons:…”
Section: Origin Of Intrinsically Ultralow Thermal Conductivitymentioning
confidence: 99%
See 4 more Smart Citations
“…clarified that the above mentioned “minimum thermal conductivity” in I‐V‐VI 2 semiconductors is limited solely by phonon‐phonon interactions [57] . Many studies have been performed to rationalize such a high thermal resistance, [53,57–60] and, as schematically shown in Figure 3, the underlying physical origins can be assigned to the following three reasons:…”
Section: Origin Of Intrinsically Ultralow Thermal Conductivitymentioning
confidence: 99%
“…In AgSbSe 2 , the valence electron configuration of Sb is 5 s 2 5p 3 , wherein only 5p 3 electrons are sharing to form a polar covalent bond with Se valence electrons while the 5s 2 electrons of Sb becomes a lone pair. [53,60,62] Numerous studies [41,56,58,59,63,64] have unambiguously demonstrated that the strong hybridization and repulsion between the lone-pair 5s 2 electrons of the group V cation and the valence p orbitals of the group VI anion lead to soft phonon modes and therefore reduced thermal conductivity. 3) Strong phonon-phonon interactions resulting from the high degree of anharmonicity in SbÀ Se bonding arrangement.…”
Section: Origin Of Intrinsically Ultralow Thermal Conductivitymentioning
confidence: 99%
See 3 more Smart Citations